Effects Of Peat Soil Carbon As Reinforcement On The Microstructure And Density In Recycled Aluminium Chips AA6061 - MOHD RAES, MOHAMAD EZZUAN BIN; mustapa, mohammad sukri (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The reinforcement materials on aluminium metal matrix composites are widely used in manufacturing sector due to lightweight, superior strength-to-weight ratio, better fracture toughness, and improved the mechanical properties. This study investigates the effect on composition of peat soil as reinforcement on AA6061 aluminium chip to physical properties of metal matrix composite. AA6061 aluminium chip reinforced with peat soil at various composition prepared by using cold compaction method were investigated. Due to the lower energies consumption and operating cost compared to conventional recycling by casting, this method was applied to study the physical properties of metal matrix composite samples. As a result, the addition of composition of peat soil shows improvement in term physical properties for composite compared to unreinforced AA6061 aluminium chip. The physical properties on density of metal matrix composites samples shows the increment up to 7.5 wt.% of peat soil, and then decreased at increasing mass fraction of peat soil. The addition of peat soil as reinforcement material shows the improvement on metal matrix composite samples.